Organic composite flexible quantum dot detector for heart rate monitoring and preparation method thereof

By introducing organic polymer barrier layers and zinc oxide nanoparticles into flexible quantum dot detectors, the problems of complex preparation and high dark currents are solved, and the effects of low dark currents and high gains are achieved, which are suitable for heart rate monitoring and other applications.

CN119836114AActive Publication Date: 2025-04-15UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510029154.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-15
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The preparation process of traditional short-wave infrared photodetectors is complex and costly, and it is difficult to apply to the living field. The surface defects of quantum dots lead to an increase in dark current, affecting detection efficiency.

Method used

The organic polymer barrier layer is introduced into the flexible quantum dot detector, which reduces the dark current of the device through the design of organic-inorganic composite materials, and uses zinc oxide nanoparticles to increase the carrier life and improves the gain of the device.

Benefits of technology

It effectively reduces the dark current of the detector, improves the gain of the device, and enables it to show good performance in applications such as heart rate monitoring, and is suitable for the preparation of wearable devices due to the use of flexible substrates.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836114A_ABST
    Figure CN119836114A_ABST
Patent Text Reader

Abstract

The invention discloses an organic composite flexible quantum dot detector for heart rate monitoring and a preparation method thereof, and belongs to the technical field of photoelectric detectors. The structure comprises a flexible substrate, a transparent electrode, an electron transport layer, a quantum dot absorption layer, an organic polymer barrier layer, a hole transport layer and a top electrode. The organic polymer barrier layer is arranged in the device to enhance blocking of external electron injection, and a depletion region is formed at the interface of the absorption layer and the organic layer, so that a conductive channel in the two films is narrowed, and the dark current is greatly reduced. The organic polymer barrier layer is added, the quantum dot material is combined with the flexible substrate, the low-dark-current organic composite flexible quantum dot detector is manufactured, the dark current of the device is reduced, meanwhile, the mechanical flexibility of the quantum dot material is beneficial to the preparation of a wearable photoelectric detector, and the photoelectric detector is suitable for large-scale production. Therefore, the method has a wide application prospect in human health signal detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of photoelectric detectors, and in particular relates to a low dark current organic composite flexible quantum dot detector and a preparation method thereof. Background Art

[0002] The core function of photodetectors is to convert captured light signals into electrical signals that can be processed by electronic devices. Based on the wavelength range of the detected light, photodetectors can be divided into three main types: ultraviolet light response detectors, visible light response detectors, and infrared light response detectors. Traditional short-wave infrared photodetectors, such as indium gallium arsenide detectors, are difficult to apply to various fields of life due to their complex preparation process and high preparation cost. The advantages of photodetectors based on quantum dot materials include low manufacturing cost, adjustable detection wavelength, and compatibility with flexible and lightweight devices. At the same time, the mechanical flexibility of quantum dot materials is conducive to the preparation of wearable photodetectors, which gives them broad application prospects in the detection of human health signals.

[0003] Among many infrared quantum dot materials, PbSe quantum dots not only have narrower bandgap and wider spectral control range, but also have larger exciton Bohr radius and significant multi-exciton effect. However, there are many defects on the surface of quantum dots, which leads to an increase in the dark current of the detector. An organic polymer barrier layer is set in the device to enhance the blocking of external electron injection. At the same time, a depletion region is formed at the interface between the absorption layer and the organic layer, which leads to the narrowing of the conductive channel in the two films, so the dark current is greatly reduced. Summary of the invention

[0004] Based on the above background technology, the present invention mainly introduces an organic polymer barrier layer into a flexible quantum dot detector to produce a low dark current organic composite flexible quantum dot detector for heart rate monitoring.

[0005] The present invention also provides an organic composite flexible quantum dot detector for heart rate monitoring, the detector comprising: a flexible substrate, a transparent electrode, an electron transport layer, a PbSe quantum dot absorption layer, an organic polymer barrier layer, a hole transport layer, and a top electrode stacked in sequence;

[0006] The transparent electrode is indium tin oxide (ITO) with a thickness of 200 nm, and the flexible substrate is polyethylene terephthalate (PET) with a thickness of 0.05 mm.

[0007] A method for preparing an organic composite flexible quantum dot detector for heart rate monitoring, the method comprising:

[0008] S1: Clean the flexible substrate with transparent electrodes in a UV-ozone cleaning machine;

[0009] S2: Spin coating zinc oxide nanoparticles on a flexible substrate to make an electron transport layer;

[0010] S3: synthesize PbSe quantum dot material, prepare it into a solution and spin-coat it on the electron transport layer, spin-coat four layers to prepare a PbSe quantum dot absorption layer film;

[0011] S4: using chlorobenzene to prepare an organic polymer solution, and spin coating it on the PbSe quantum dot absorption layer to obtain an organic thin film barrier layer;

[0012] S5: using a vacuum evaporation method to deposit molybdenum trioxide on the organic thin film barrier layer to obtain a hole transport layer;

[0013] S6: The top electrode silver is prepared on the surface of the hole transport layer by vacuum evaporation to obtain a flexible quantum dot detector.

[0014] Specifically, the spin-coated zinc oxide nanoparticle film is rotated at a rotation speed of 3000 rpm for 60 seconds and then annealed at 100° C. for 1 hour, wherein the mass percentage of the zinc oxide nanoparticles is 2.5 wt.%.

[0015] Specifically, the preparation method of the PbSe quantum dot material in step S3 is:

[0016] Step a: Preparation of selenium precursor: 0.64 g (8 mmol) of selenium powder and 6.4 ml of tri-n-octylphosphine were mixed and stirred in a sealed environment for 12 h, wherein the concentration of the mixture of selenium powder and tri-n-octylphosphine was 1.25 mmol / ml;

[0017] Step b: Preparation of lead precursor: 0.892 g (4 mmol) of lead oxide, 2.7 ml of oleic acid, and 16 ml of 1-octadecene are mixed, wherein the molar ratio of lead oxide to selenium powder is 1:2, the volume ratio of oleic acid to 1-octadecene solution is 27:160, and the mixed concentration of lead oxide and 1-octadecene is 0.25 mmol / ml; the three-necked flask containing the lead precursor is placed in a heating mantle, the temperature is set to 30°C, vacuuming for 25 minutes, filling with nitrogen for 15 minutes, and vacuuming-filling with nitrogen is repeated three times until the mixture is completely in a nitrogen environment; slowly heating to 110°C at a rate of 60°C / h in a nitrogen environment and staying at this temperature for 15 minutes;

[0018] Step c: Synthesis reaction, heating to 160°C at a rate of 60°C / h, injecting the selenium precursor into the mixed solution prepared in step b, reacting for 3 minutes, injecting n-hexane for quenching, wherein the ratio of n-hexane to selenium powder is 1.6mmol / ml; when the temperature drops to 60°C, adding ammonium chloride methanol solution with a concentration of 10.7mg / ml, wherein the ratio of ammonium chloride methanol solution to selenium powder is 4mmol / ml, and cooling to 35°C;

[0019] Step d: separation and purification, preparing a centrifuge solution with isopropanol and acetone in a ratio of 2:1, mixing the stock solution obtained in step c with the centrifuge solution in a ratio of 1:3, and centrifuging again, obtaining quantum dots on the side wall of the centrifuge tank, dissolving the side wall quantum dots with n-hexane, and then centrifuging and drying to obtain dry PbSe quantum dots;

[0020] Step e: prepare the solution, and select n-octane as the solvent to prepare a 50 mg / ml PbSe quantum dot solution.

[0021] Specifically, when the PbSe quantum dot material is spin-coated, the PbSe quantum dots are first coated and rotated at a speed of 1500rpm for 60s; then a 2% EDT acetonitrile solution is dripped to cover the entire surface of the device film, and the long-chain oleic acid is allowed to stand for 45s to be fully replaced by the short-chain EDT, and then rotated at 1500rpm for 30s to ensure that the film is uniform; finally, acetonitrile is dripped on the surface of the film to clean the ligand, and rotated at 1500rmp for 30s. This cleaning step is repeated three times to ensure that the residual solute is completely removed. The above process is repeated four times, which is equivalent to coating four layers of quantum dots, and finally annealed at 100°C for 5 minutes on a heating table.

[0022] Specifically, the spin-coated organic polymer is P3HT with a concentration of 15 mg / ml, which is rotated at 3000 rpm for 60 seconds and then annealed on a heating stage at 100° C. for 10 minutes.

[0023] Specifically, the vacuum evaporation pressure is 10 -4 Pa.

[0024] The beneficial effects of the present invention are:

[0025] The present invention proposes a low dark current organic composite flexible quantum dot detector and a preparation method thereof, wherein an organic polymer barrier layer is added to form an organic-inorganic composite to reduce the dark current of the device; zinc oxide nanoparticles are used to increase the carrier lifetime, thereby improving the gain of the device; PbSe quantum dots are used as the absorption layer of the device, and the absorption wavelength can be adjusted to broaden the detection wavelength; a flexible substrate is used, which can be applied to wearable devices for heart rate monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a schematic diagram of the structure of the low dark current organic composite flexible quantum dot detector of the present invention.

[0027] Figure 2 It is the absorption spectrum of the PbSe quantum dots synthesized in the present invention.

[0028] Figure 3 This is a dark current test diagram of the low dark current organic composite flexible quantum dot detector of the present invention.

[0029] Figure 4This is a current-voltage test diagram of the low dark current organic composite flexible quantum dot detector of the present invention.

[0030] Figure 5 This is a heart rate monitoring image of our low dark current organic composite flexible quantum dot detector. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and beneficial effects of the present invention clearer and more complete, the present invention is further described with reference to the following examples and drawings.

[0032] Example 1

[0033] The present invention provides a low dark current organic composite flexible quantum dot detector and a preparation method thereof. The specific preparation method comprises the following steps:

[0034] S1: The flexible substrate with a transparent electrode is placed in a UV ozone cleaning machine for 20 minutes, wherein the transparent electrode is indium tin oxide (ITO) with a thickness of 200 nm, and the flexible substrate is polyethylene terephthalate (PET) with a thickness of 0.05 mm;

[0035] S2: preparing an electron transport layer, spin coating zinc oxide nanoparticles, rotating at 3000 rpm for 60 seconds, and then annealing at 100° C. for 1 hour, wherein the mass percentage of zinc oxide nanoparticles is 2.5 wt.% (crystalline ZnO in 2-propanol);

[0036] S3: Make an absorption layer film, synthesize PbSe quantum dot material, configure it into a solution and spin-coat it on the electron transport layer. When spin-coating the PbSe quantum dot material, first apply the PbSe quantum dots and rotate at a speed of 1500rpm for 60s; then add 2% EDT acetonitrile solution to cover the entire surface of the device film, let it stand for 45s to allow the long-chain oleic acid to be fully replaced by the short-chain EDT, and then rotate at 1500rpm for 30s to ensure that the film is uniform; finally, add acetonitrile to the surface of the film to clean the ligand, and rotate at 1500rmp for 30s. Repeat this cleaning step three times to ensure that the residual solute is completely removed. The above process is repeated four times, which is equivalent to applying four layers of quantum dots, and finally annealing at 100°C for 5 minutes on a heating table;

[0037] S4: Making a barrier layer, the organic polymer is P3HT, the solvent is chlorobenzene, the solution concentration is 15 mg / ml, the rotation speed is 3000 rpm, the rotation is 60 seconds, and then annealed on a heating table at 100°C for 10 minutes;

[0038] S5: Make the electron blocking layer of molybdenum trioxide by vacuum evaporation. The evaporation pressure of vacuum evaporation is 10 -4 Pa, the thickness of the electron blocking layer is 10 nm;

[0039] S6: Make the top electrode silver by vacuum evaporation. The evaporation pressure of vacuum evaporation is 10 -4 Pa, with a thickness of 100 nm, a flexible quantum dot detector was obtained.

[0040] In s3, the synthesized PbSe quantum dot material specifically comprises:

[0041] For the preparation of selenium precursor, 0.64 g of selenium powder (8 mmol) and 6.4 ml of tri-n-octylphosphine were mixed and stirred overnight in a glove box. For the preparation of lead precursor, 0.892 g (4 mmol) of lead oxide was mixed with 2.7 ml of oleic acid and 16 ml of 1-octadecene; the mixture was vacuumed for 25 min at 30 °C and filled with nitrogen for 15 min. This step was repeated 3 times. In a nitrogen environment, the temperature was slowly increased to 110°C at intervals of 20°C and maintained for 10 min. For synthesis reaction, the temperature was increased to 160°C at intervals of 20°C, and the selenium precursor was injected. After the reaction was continued for 3 min, 5 ml of n-hexane was injected to quench. When the temperature dropped to 60°C, 2 ml of 10.7 mg / ml ammonium chloride methanol solution was added, and the mixture was cooled to 35°C. For separation and purification, a centrifuge solution was prepared with isopropanol and acetone in a ratio of 2:1, and 2 ml of the original solution + 6 ml of the centrifuge solution was used for centrifugation. The side wall quantum dots were dissolved with n-hexane, and the mixture was centrifuged 3-4 times to dry. For solution preparation, n-octane was selected as the solvent to prepare a 50 mg / ml PbSe quantum dot solution.

[0042] The performance characterization test of the device prepared in this embodiment is as follows:

[0043] A schematic diagram of the structure of a low dark current organic composite flexible quantum dot detector is shown in Figure 1 As shown, (1) a flexible substrate, (2) a transparent electrode, (3) an electron transport layer, (4) a PbSe quantum dot absorption layer, (5) an organic polymer blocking layer, (6) a hole transport layer, and (7) a top electrode. The organic polymer blocks electrons from the top electrode, thereby reducing the dark current of the device; the organic-inorganic composite is spin-coated on the quantum dot absorption layer, and a depletion region is formed at the interface between the absorption layer and the organic layer, resulting in a narrowing of the conductive channel in the two films, thereby greatly reducing the dark current. The wide-bandgap zinc oxide nanoparticles and quantum dots prepared by surface ligand modification are used to construct a heterojunction, and the zinc oxide nanoparticles can be annealed at a lower temperature so that they can be prepared on a flexible substrate. The introduced zinc oxide nanoparticles can increase the carrier lifetime, thereby improving the gain of the device. The photodetector is made using a flexible substrate, and each layer in the device can be annealed at a low temperature, thereby realizing the heart rate monitoring function.

[0044] The absorption spectrum of PbSe quantum dots is shown in Figure 2 As shown, its absorption peak is at 1700nm.

[0045] The dark current characteristics of the detector are as follows Figure 3 As shown, by adding an organic polymer barrier layer, the dark current is reduced by an order of magnitude.

[0046] The current JV characteristics of the detector are as follows: Figure 4 As shown, under reverse bias, the photocurrent density at 1550nm is 5.7×10 -3 A.cm -2 , the dark current density is 1.2×10 -5 A.cm -2 .

[0047] Figure 5 This is a heart rate monitoring chart of the flexible device, showing the heart rate fluctuation within 10 seconds.

[0048] The present invention adds an organic polymer barrier layer and combines the quantum dot material with a flexible substrate to produce a low dark current organic composite flexible quantum dot detector, which reduces the dark current of the device. At the same time, the mechanical flexibility of the quantum dot material is conducive to the preparation of wearable photoelectric detectors, giving it broad application prospects in human health signal detection.

[0049] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. An organic composite flexible quantum dot detector for heart rate monitoring, the detector comprising: a flexible substrate, a transparent electrode, an electron transport layer, a PbSe quantum dot absorption layer, an organic polymer barrier layer, a hole transport layer, and a top electrode stacked in sequence; The transparent electrode is indium tin oxide with a thickness of 200nm, and the flexible substrate is polyethylene terephthalate with a thickness of 0.05mm.

2. A method for preparing an organic composite flexible quantum dot detector for heart rate monitoring, the method comprising: S1: Clean the flexible substrate with transparent electrodes in a UV-ozone cleaning machine; S2: Spin coating zinc oxide nanoparticles on a flexible substrate to make an electron transport layer; S3: synthesize PbSe quantum dot material, prepare it into a solution and spin-coat it on the electron transport layer, spin-coat four layers to prepare a PbSe quantum dot absorption layer film; S4: using chlorobenzene to prepare an organic polymer solution, and spin coating it on the PbSe quantum dot absorption layer to obtain an organic thin film barrier layer; S5: using a vacuum evaporation method to deposit molybdenum trioxide on the organic thin film barrier layer to obtain a hole transport layer; S6: The top electrode silver is prepared on the surface of the hole transport layer by vacuum evaporation to obtain a flexible quantum dot detector.

3. The method for preparing an organic composite flexible quantum dot detector for heart rate monitoring according to claim 2, characterized in that: The spin-coated zinc oxide nanoparticle film was rotated at a rotation speed of 3000 rpm for 60 seconds and then annealed at 100° C. for 1 hour, wherein the mass percentage of the zinc oxide nanoparticles was 2.5 wt.%.

4. The method for preparing an organic composite flexible quantum dot detector for heart rate monitoring according to claim 2, characterized in that: The preparation method of the PbSe quantum dot material in step S3 is: Step a: Preparation of selenium precursor: 0.64 g of selenium powder and 6.4 ml of tri-n-octylphosphine were mixed and stirred in a sealed environment for 12 h, wherein the concentration of the mixture of selenium powder and tri-n-octylphosphine was 1.25 mmol / ml; Step b: Preparation of lead precursor: 0.892 g of lead oxide, 2.7 ml of oleic acid and 16 ml of 1-octadecene are mixed, wherein the molar ratio of lead oxide to selenium powder is 1:2, the volume ratio of oleic acid to 1-octadecene solution is 27:160, and the mixed concentration of lead oxide and 1-octadecene is 0.25 mmol / ml; the three-necked flask containing the lead precursor is placed in a heating mantle, the temperature is set to 30°C, vacuuming for 25 minutes, filling with nitrogen for 15 minutes, and vacuuming-filling with nitrogen is repeated three times until the mixture is completely in a nitrogen environment; slowly heating to 110°C at a rate of 60°C / h in a nitrogen environment and staying at this temperature for 15 minutes; Step c: Synthesis reaction, heating to 160°C at a rate of 60°C / h, injecting the selenium precursor into the mixed solution prepared in step b, reacting for 3 minutes, injecting n-hexane for quenching, wherein the ratio of n-hexane to selenium powder is 1.6mmol / ml; when the temperature drops to 60°C, adding ammonium chloride methanol solution with a concentration of 10.7mg / ml, wherein the ratio of ammonium chloride methanol solution to selenium powder is 4mmol / ml, and cooling to 35°C; Step d: separation and purification, preparing a centrifuge solution with isopropanol and acetone in a ratio of 2:1, mixing the stock solution obtained in step c with the centrifuge solution in a ratio of 1:3, and centrifuging again, obtaining quantum dots on the side wall of the centrifuge tank, dissolving the side wall quantum dots with n-hexane, and then centrifuging and drying to obtain dry PbSe quantum dots; Step e: prepare the solution, and select n-octane as the solvent to prepare a 50 mg / ml PbSe quantum dot solution.

5. The method for preparing an organic composite flexible quantum dot detector for heart rate monitoring according to claim 2, characterized in that: When the PbSe quantum dot material is spin-coated, the PbSe quantum dots are first coated and rotated at a speed of 1500rpm for 60s; then a 2% EDT acetonitrile solution is dripped to cover the entire surface of the device film, and the long-chain oleic acid is allowed to be fully replaced by the short-chain EDT, and then rotated at 1500rpm for 30s to ensure that the film is uniform; finally, acetonitrile is dripped on the surface of the film to clean the ligand, and rotated at 1500rmp for 30s. This cleaning step is repeated three times to ensure that the residual solute is completely removed. The above process is repeated four times, which is equivalent to coating four layers of quantum dots, and finally annealed at 100°C for 5 minutes on a heating table.

6. The method for preparing an organic composite flexible quantum dot detector for heart rate monitoring according to claim 2, characterized in that: The spin-coated organic polymer was P3HT with a concentration of 15 mg / ml, which was spun at 3000 rpm for 60 seconds and then annealed on a heating stage at 100° C. for 10 minutes.

7. The method for preparing an organic composite flexible quantum dot detector for heart rate monitoring according to claim 2, characterized in that: The vacuum evaporation pressure is 10 -4 Pa.

Citation Information

Patent Citations

  • Organic photovoltaic cell based on inorganic quantum dot and preparing method

    CN103904224A

  • Preparation method of flexible self-driven heart rate monitoring equipment

    CN118843372A

  • Photoelectric detector based on paper-based flexible conductive substrate and preparation method thereof

    CN119069566A

  • Organic photoelectric detector based on quantum dot active layer processing strategy and preparation method thereof

    CN119156024A